Supercritical extraction of costus spicatus leafs combined with ultrasound pretreatment: experimentation and modeling - Laurintino, Thaíris Karoline Silva (2024)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Química, Florianópolis, 2024.